Hardware implementation of modulo multipliers for international data encryption algorithm - Liao, Jia. (2009)
Keeping the information secret is one of the key functions of cryptography. In recent years, a lot of research is done in the area of block cipher algorithms. International Data Encryption Algorithm (IDEA) is one of the most reliable block cipher algorithm.